Optical microfiber-based sensor and pulse fiber laser incorporating graphene saturable absorber / Muwafaq Fadhil Jaddoa - Muwafaq Fadhil , Jaddoa (2017)
As part of the work presented in this thesis, optical microfibers have been fabricated, characterized and studied in detail. These microfibers have a compact structure, a fast response time, and a strong evanescent field effect and enable facile waveguide fabrication through the reduction of the single-mode fiber diameter. Two methods have been used to fabricate the optical microfibers: a heat-and-pull method using a flame and a heat-and-pull method using a microheater. These methods’ advantages lie in their wide array of applications, such as optical sensors and communications. For this study, experimental studies on optical sensors based on optical microfibers (OMFs) were conducted, focusing on the use of inline microfiber Mach-Zehnder interferometer (IMMZI)-based sensors. The responses of IMMZI sensors with various diameters and for various refractive indices of the surrounding medium have been analyzed and experimentally investigated. In addition, an IMMZI was also used to tune single-wavelength erbium-doped fibers (EDFs) based on the stretching technique. The effects of increasing and decreasing the strain force on the IMMZI were also observed. Because of their many uses, additional potential applications based on the interaction of an optical microfiber’s evanescent field with saturable absorbers were also experimentally studied. To serve as passive saturable absorbers, graphene and graphene oxide were deposited or fabricated as a thin film to be utilized in an optical microfiber cavity to generate EDF-based multi-wavelength, Q-switched and mode-locked lasing. The optical microfiber acted as a multi-modal interference medium to form an optical-wavelength-selective filter.